Cross-shore sorting on a beach under wave action - Celikoglu, Yesim; Yuksel, Yalcin; Kabdasli, M. Sedat (COASTAL EDUCATION & RESEARCH FOUNDATION, 2006)
Sorting of sediment on a beach occurs when the cross-shore profile consists of graded sediments. Each grain-size fraction within a mixture responds differently to the same hydrodynamic regime. Sorting of sediment under wave action takes several forms. Stratified layers of finer and coarser sediment are formed, depending on wave climate, grain size, and beach slope. Grain size and sorting studies are of great importance in characterizing the dynamic beach environment. Some field data have been reported in the literature. In the present study, the cross-shore distribution of sediments, as well as the corresponding beach profiles, were measured in a wave basin on 1:5 beach slope for regular waves. Eighteen sets of experiments were performed on cross-shore sorting mechanisms using two different sand beds. The sorting of bed material and the formation of armor coats along beach profiles were defined by grain-size distribution and dimensionless parameters in this study. The experiments showed that finer material was deposited on the crest of bar-type beach profiles, but coarser grains accumulated on the foreshore, trough, ridge, and toe sections. Finer materials settled on the foreshore and crest of step-type profiles while coarser grains were deposited on the ridge and toe sections. The effect of the movement of a particular fraction on the sediment transport rate was also studied. Calculated sediment transport, modified to include the effects of sorting, was compared with transport rates measured in the wave basin. This suggested that the results under the experimental conditions were satisfactory for the description of sediment transport in the surf zone using the partial sediment transport mechanism over the beach profiles.
Keywords: cross-shore transport; coastal morphology; coastal sediment transport; cross-shore sorting of sediment; GRAIN-SIZE; SEDIMENT; TRANSPORT; MOTION; Environmental Sciences & Ecology; Physical Geography; Geology